Evaluation of mixed adsorbents for the removal of arsenic(III) from wastewater - Srivastava K.K.; Singh A.P.; Shekhar H. (My University, 2025)
Utilization of red mud and its (1 : 1) mixture by weight with haematite, china clay, fly ash and china clayfly ash mixed adsorbents has been made for the removal of arsenic(III) from waste water at different operating parameter such as adsorbate and adsorbent dose, particle size of adsorbent and agitation speed. The percentage removal of AsIII has been found optimum at lower concentration and increase in adsorbent dose and decrease in particle size at 220 rpm of agitation speed.